It Capacity Improvement for Swimming Coaches and Assistant Coaches for Swimming Performance Coaching at the Indonesian Aquatic Federation in Magelang City - Akhlak, Muhammad Lutfi Mahasinul; Kanafi, Kanafi; Syaifullah, Rony (Pascasarjana Universitas Mataram, 2024)
Swimming is a water sport that is quite popular with the public to maintain and improve health and is also a branch of achievement sports that are competed in national, regional and international events. The main key to helping athletes achieve success is a competent coach. Coaches who are experts in their fields will find it easier to create and implement training programs to help athletes achieve success. This community service activity is carried out using training and mentoring methods with stages of socialization, training, technology application, mentoring and evaluation and program sustainability. Based on the success indicators obtained from the monitoring and evaluation stages, the results showed that 90% of swimming coaches and assistant coaches already understood the importance of using information technology. 75% of coaches and assistant coaches are skilled in using information technology even though they encounter obstacles. 75% of coaches are able to practice using the Computational Fluid Dynamics Methodology and 80% of coaches are willing to socialize the application of information technology in swimming to colleagues